Adult exposure to acidified seawater influences sperm physiology in Mytilus galloprovincialis: Laboratory and in situ transplant experiments. (October 2020) - Gallo, Alessandra; Esposito, Maria Consiglia; Cuccaro, Alessia; Buia, Maria Cristina; Tarallo, Andrea; Monfrecola, Vincenzo; Tosti, Elisabetta; Boni, Raffaele
Abstract: The ongoing increase of CO2 in the atmosphere is inducing a progressive lowering of marine water pH that is predicted to decrease to 7.8 by the end of this century. In marine environment, physical perturbation may affect reproduction, which is crucial for species' survival and strictly depends on gamete quality. The effects of seawater acidification (SWAc) on gamete quality of broadcast spawning marine invertebrates result largely from experiments of gamete exposure while the SWAc impact in response to adult exposure is poorly investigated. Performing microcosm and in field experiments at a naturally acidified site, we investigated the effects of adult SWAc exposure on sperm quality parameters underlying fertilization in Mytilus galloprovincialis . These animals were exposed to pH 7.8 over 21 days and collected at different times to analyze sperm parameters as concentration, motility, viability, morphology, oxidative status, intra- and extra-cellular pH and mitochondrial membrane potential. Results obtained in the two experimental approaches were slightly different. Under field conditions, we found an increase in total sperm motility and mitochondrial membrane potential on days 7 and 14 from the start of SWAc exposure whereas, in microcosm, SWAc group showed an increase of total motility on day 14. In addition, sperm morphology and intracellular pH were affected in both experimental approaches; whereas oxidative stress was detected only in spermatozoa collected from mussels under natural SWAc. The overall analysis suggests that, in mussels, SWAc toxic mechanism in spermatozoa does not involve oxidative stress. This study represents the first report on mussel sperm quality impairment after adult SWAc exposure, which may affect fertilization success with negative ecological and economic consequences; it also indicates that, although naturally acidified areas represent ideal natural laboratories for investigating the impact of ocean acidification, microcosm experiments are necessary for examining action mechanisms. Graphical abstract: Image 1 Highlights: SWAc impacts on sperm physiology in the M. galloprovincialis after paternal exposure. Microcosm and in situ transplant experiment were set up and compared. Several sperm quality parameters were analyzed at different exposure times. Paternal SWAc exposure affects sperm motility, morphology, mitochondria and pHi . Microcosm experiments allowed to explore mechanism underlying responses to SWAc. Abstract : Seawater acidification exposure on adult mussels affects sperm motility, morphology, mitochondrial activity and pHi through mechanisms that are not likely associated to oxidative stress.